2004
DOI: 10.1152/ajplung.00454.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic ADP-ribose, a putative Ca2+-mobilizing second messenger, operates in submucosal gland acinar cells

Abstract: Cyclic ADP-ribose (cADPR), a putative Ca(2+)-mobilizing second messenger, has been reported to operate in several mammalian cells. To investigate whether cADPR is involved in electrolyte secretion from airway glands, we used a patch-clamp technique, the measurement of microsomal Ca(2+) release, quantification of cellular cADPR, and RT-PCR for CD38 mRNA in human and feline tracheal glands. cADPR (>6 microM), infused into the cell via the patch pipette, caused ionic currents dependent on cellular Ca(2+). Infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 64 publications
1
26
0
Order By: Relevance
“…]i. Moreover, we found that physiologically relevant, basic secretions from swine tracheal submucosal glands could be triggered by ϳ30 nM of ACh (16,17,31,38,39,44,45). The viability of all tested cells was confirmed by the occurrence of ionic responses after the subsequent addition of 30 nM of ACh.…”
Section: Potentiating Effects Of Flagellin On Ach-induced Ionic Currementioning
confidence: 70%
See 4 more Smart Citations
“…]i. Moreover, we found that physiologically relevant, basic secretions from swine tracheal submucosal glands could be triggered by ϳ30 nM of ACh (16,17,31,38,39,44,45). The viability of all tested cells was confirmed by the occurrence of ionic responses after the subsequent addition of 30 nM of ACh.…”
Section: Potentiating Effects Of Flagellin On Ach-induced Ionic Currementioning
confidence: 70%
“…The isolated glands were further dispersed enzymatically by incubating them with enzyme solution containing collagenase (200 U/ml) and DL-DTT (0.31 mg/ml) for 30 min at 37°C. After dispersion and a wash with centrifugation at 180 g, the cells were resuspended in a standard extracellular solution until use, as reported previously (16,17,31,38,39,44,45). In a series of experiments investigating the effect of blocking antibodies, anti-TLR 5 polyclonal antibody (10 g/ml) or nonspecific IgG (10 g/ml) was also preincubated with cells for 1 h at 37°C before use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations